New Sunday Times, 25 April 2009 (NSTP, 2009)
He is getting his just dues today . And about time too. Syed Ahmad Faizal Syed Fadzil Al-Attas, better known as Pacai, has over the year, won a triple platinum award with Ekamatra, rubbed musical shoulders with world famous Indian composer A.R.Rahman, backed up the ever popular Sheila Majid and had gone on stage with Zainal Abidin in Japan.